Natural History of Coronavirus Disease 2019: Risk Factors for Hospitalizations and Deaths Among >26 Million US Medicare Beneficiaries. (16th December 2020) - Izurieta, Hector S; Graham, David J; Jiao, Yixin; Hu, Mao; Lu, Yun; Wu, Yue; Chillarige, Yoganand; Wernecke, Michael; Menis, Mikhail; Pratt, Douglas; Kelman, Jeffrey; Forshee, Richard
Abstract: Background: The current study was performed to evaluate risk factors for severe coronavirus disease 2019 (COVID-19) outcomes among Medicare beneficiaries during the pandemic's early phase. Methods: In a retrospective cohort study covering Medicare fee-for-service beneficiaries, we separated out elderly residents in nursing homes (NHs) and those with end-stage renal disease (ESRD) from the primary study population of individuals age ≥65 years. Outcomes included COVID-19 hospital encounters and COVID-19-associated deaths. We estimated adjusted odds ratios (ORs) using logistic regression. Results: We analyzed 25 333 329 elderly non-NH beneficiaries without ESRD, 653 966 elderly NH residents, and 292 302 patients with ESRD. COVID-related death rates (per 10 000) were much higher among elderly NH residents (275.7) and patients with ESRD (60.8) than in the primary study population (5.0). Regression-adjusted clinical predictors of death among the primary population included immunocompromised status (OR, 1.43), frailty index conditions such as cognitive impairment (3.16), and other comorbid conditions, including congestive heart failure (1.30). Demographic-related risk factors included male sex (OR, 1.77), older age (3.09 for 80- vs 65-year-olds), Medicaid dual-eligibility status (2.17), and racial/ethnic minority. Compared with whites, ORs were higher for blacks (2.47), Hispanics (3.11), and Native Americans (5.82). Results for COVID-19 hospital encounters were consistent. Conclusions: Frailty, comorbid conditions, and race/ethnicity were strong risk factors for COVID-19 hospitalization and death among the US elderly. Abstract : This observational study quantified the degree of elevated risk of coronavirus disease 2019–associated deaths and hospitalizations among elderly Medicare beneficiaries who were older, male, of lower socioeconomic status, or immunocompromised or who had comorbid conditions. Risk was also substantially higher among nursing home residents and those with end-stage renal disease.